Domain Wall Coupling in Ferromagnetic/Ferroelectric Heterostructures: Scaling Behaviour and Electric Field Driven Motion - Franke, Kévin (Aalto University, 2016)
Ferromagnetic and ferroelectric materials exhibit an order parameter that can be controlled and switched with an external field conjugate to it. This property has been used in practical applications such as memory devices or sensors. In an effort to further scale down the size and energy consumption of devices, multiferroic materials are investigated. In these materials multiple ferroic orders coexist and coupling between them allows tailoring of magnetic properties in an electric field or vice versa. The observation of novel physical phenomena and the promise of new device concepts make these materials attractive. However, due to the incompatibility of the conventional mechanisms that give rise to ferromagnetism and ferroelectricity, strong coupling of sizeable order parameters at room temperature is difficult to obtain in single phase materials. A promising alternative is the use of hybrid material systems, such as thin film hetero-structures, where ferromagnetic and ferroelectric compounds are artificially assembled. In this Thesis I present results on elastically coupled domain walls in ferromagnetic/ferroelectric heterostructures. BaTiO3 substrates exhibiting regular ferroelastic stripe domains are used as the ferroelectric component. Ferromagnetic thin films or multilayers are deposited using Electron Beam Evaporation, Magnetron Sputtering, or Molecular Beam Epitaxy depending on the material. The heterostructures are investigated by Magneto-Optical Kerr Effect (MOKE) microscopy and Scanning Electron Microscopy with Polarisation Analysis (SEMPA). Micro-magnetic simulations and analytical modelling complement and expand upon the experimental results. Strain transfer from the laterally modulated ferroelectric domains in the substrate induces an-isotropies in the ferromagnetic thin films via inverse magnetostriction. The abrupt changes in symmetry and orientation of these anisotropies on top of ferroelectric domain boundaries lead to strong pinning of magnetic domain walls. As a result, two types of domain walls - uncharged and charged - can be initialised. They differ in width, energy, and chirality and are tuned by magnetic fields. The remanent magnetisation and switching behaviour of the films are strongly affected by these domain walls when the dimensions of the domains are scaled down to a length comparable to the width of the domain walls. In an electric field, both in-plane and alternating in-plane/out-of-plane magnetic domain patterns can be rewritten. Finally, controlled and reversible electric field induced magnetic domain wall motion is demonstrated. This novel driving mechanism functions without the use of spin polarised currents or magnetic fields. As a result, high density and low power devices based on magnetic domain walls can be envisaged.
Keywords: Physics; ferromagnetism; ferroelectricity; multiferroic; magnetism; magnetic domains; magnetic domain walls; spintronics; electric field control of magnetism